A control laboratory plant to experiment with hybrid systems - Gambier, Adrián; Miksch, Tobias; Badreddin, Essameddin (Proceedings of the 2003 American Control Conference, 2003)
A multivariable test-bed for research and teaching in hybrid system is presented. The process control laboratory plant uses standard industrial components, which introduces more realism and robustness into the experiments with hybrid systems. The paper describes the plant, mathematical modeling of the system and an illustrative experiment. Moreover, criteria for the selection of the hardware/software platform for the real-time implementation are given. Although the plant was developed thinking in hybrid system research, many simple experiments can be implemented for educational purposes.